Red Dragon (Hannibal Lecter book 1) - Thomas Harris (New York The Berkley Publishing Group, 2009)
Red Dragon is a novel by American author Thomas Harris, first published in 1981. The plot follows former FBI profiler Will Graham, who comes out of retirement to find and apprehend an enigmatic serial-killer nicknamed "The Tooth Fairy". The novel introduced the character Dr. Hannibal Lecter, a brilliant psychiatrist and cannibalistic serial-killer, whom Graham reluctantly turns to for advice and with whom he has a dark past.
Keywords: Thriller; Psychological thriller